Фестивалі як прояв синергії сільського туризму в Чернівецькій області - Грицку-Андрієш, Юлія Петрівна; Бучко, Жанна Іванівна (Чернівці: Чернівецький національний університет, 2010)
Our research devoted to the interaction of tourism in rural areas to other sectors of the economy. We considered such economic activities as: folk crafts, organic farming, rural restaurants and festivals. Promotion of local festivals at the regional and national level will bring in Chernovtsy more tourists.
Festivals as a display of synergy of rural tourism in the Chernivtsi region.
Keywords: Синергія; Фестиваль; Туризм; Народні промисли; Органічне фермерство